To the Problem of the Interpretative Method in „Gospel of Christian Glory in the Apocalypse“ by N. N. Glubokovsky (Forum Theologicum Sardicense, 2025)
Nevjana Rizova, To the Problem of the Interpretative Method in “Gospel of Christian Glory in the Apocalypse” by N. N. GlubokovskyThe author provides a brief overview of Glubokovsky’s work Gospel of Christian Glory in the Apocalypse, focusing specifically on Glubokovsky’s exegetical approach to interpreting the Revelation of St. John.